Labor problems in the industrialization of India - Myers, Charles Andrew (Harvard University Press, Cambridge, Mass., 1958)
This volume is particularly noteworthy because it probably provides the first comprehensive treatment of the problems of labor and management in the explicit context of economic development.
Bibliographical references included in "Notes" (p.[241]-291)
rpm 23/02/2018
Loans
Keywords: Labour and labouring classes; India